Limnology of lake Rainkhyongkain of Bangladesh with a new record of Marchantia polymorpha L. var. aquatica Nees (Bangladesh Journal of Botany, 2014)
In lake Rainkhyongkain, water temperature, pH, conductivity and total dissolved solids (TDS) were recorded 33.5°C, 7.39, 308 ?S/cm and 49 mg/l, respectively. The mean values (n = 4) of dissolved oxygen content (DO), alkalinity, soluble reactive phosphorus (SRP), soluble reactive silicate (SRS) and NO3-N were 7.93 ± 0.78 mg/l, 1.70 ± 0.12 meq/l, 17.25 ± 0.62 ?g/l, 10.44 ± 0.72 mg/l and 34.00 ± 4.00 ?g/l, respectively. The phytoplankton biomass as chlorophyll a (chl a) was found very low (4.93 ± 0.51 ?g/l) with a phaeopigment concentration of 1.97 ± 0.51 ?g/l. A total of 16 phytoplankton taxa were recorded of which Cyclotella comensis (V. Keissler) Lemm. was dominant followed by Protoperidinium conicum (Gran) Balech, Coelosphaerium kuetzingianum Näg., Euglena spp. and Mallomonas paxillata Bardley. For the first time in Bangladesh Marchantia polymorpha L. var. aquatica Nees was found to grow in masses in the shallow littoral of the lake. Among the dominant macrophytes of the littoral, Nymphaea stellata Willd., Nymphoides indicum (L.) O. Kuntze and Monochoria hastata (L.) Solms were common. DOI: http://dx.doi.org/10.3329/bjb.v42i2.18023 Bangladesh J. Bot. 42(2): 223-229, 2013 (December)